2.2.2-Cryptand complexes of neptunium(iii) and plutonium(iii). Issue 7 (22nd December 2021) - Goodwin, Conrad A. P.; Ciccone, Sierra R.; Bekoe, Samuel; Majumdar, Sourav; Scott, Brian L.; Ziller, Joseph W.; Gaunt, Andrew J.; Furche, Filipp; Evans, William J.
Abstract : The THF-soluble [An(crypt)(OTf)2 ][OTf] complexes for An = Np and Pu were synthesized from AnI3 (THF)4 starting materials based on pilot studies of the An = U system. 5f 3 U(iii ), 5f 4 Np(iii ), and 5f 5 Pu(iii ) electron configurations are indicated by DFT analysis of their UV-visible-NIR spectra. Abstract : New coordination environments are reported for Np(iii ) and Pu(iii ) based on pilot studies of U(iii ) in 2.2.2-cryptand (crypt). The U(iii )-in-crypt complex, [U(crypt)I2 ][I], obtained from the reaction between UI3 and crypt, is treated with Me3 SiOTf (OTf = O3 SCF3 ) in benzene to form the [U(crypt)(OTf)2 ][OTf] complex. Similarly, the isomorphous Np(iii ) and Pu(iii ) complexes were obtained similarly starting from [AnI3 (THF)4 ]. All three complexes (1-An ; An = U, Np, Pu) contain an encapsulated actinide in a THF-soluble complex. Absorption spectroscopy and DFT calculations are consistent with 5f 3 U(iii ), 5f 4 Np(iii ), and 5f 5 Pu(iii ) electron configurations.